2012
DOI: 10.1038/nature10754
|View full text |Cite
|
Sign up to set email alerts
|

Neuron-type-specific signals for reward and punishment in the ventral tegmental area

Abstract: Dopamine plays a key role in motivation and reward. Dopaminergic neurons in the ventral tegmental area (VTA) signal the discrepancy between expected and actual rewards (i.e., reward prediction error, RPE)1-3, but how they compute such signals is unknown. We recorded the activity of VTA neurons while mice associated different odour cues with appetitive and aversive outcomes. We found three types of neurons based on responses to odours and outcomes: approximately half of the neurons (Type I, 52%) showed phasic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

133
1,324
9
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,172 publications
(1,506 citation statements)
references
References 36 publications
(40 reference statements)
133
1,324
9
2
Order By: Relevance
“…Quantification revealed that 40.7% (1,415/3,481) of tyrosine hydroxylase (TH)-positive neurons were positive for ChR2-YFP in the VTA. The ability of ChR2 to excite VTA DA neurons in DAT-cre mice has been previously validated (31,32).…”
Section: Resultsmentioning
confidence: 99%
“…Quantification revealed that 40.7% (1,415/3,481) of tyrosine hydroxylase (TH)-positive neurons were positive for ChR2-YFP in the VTA. The ability of ChR2 to excite VTA DA neurons in DAT-cre mice has been previously validated (31,32).…”
Section: Resultsmentioning
confidence: 99%
“…The mesocorticolimbic dopaminergic system, composed of dopaminergic neurons and their projections, has been proven to be involved in the reward‐motivated behaviors of individuals (Cohen, Haesler, Vong, Lowell, & Uchida, 2012; Ikemoto, 2007). The dopaminergic neurons are mainly located in the ventral tegmental area (VTA) (Beckstead, Domesick, & Nauta,1979) and project primarily to the prefrontal cortex (PFC), olfactory tubercle (OT), nucleus accumbens (NAc), dorsal striatum (ST), and the amygdala (AMy).…”
Section: Introductionmentioning
confidence: 99%
“…The present data strengthen a dopamine-suppressive action of aversive stimuli that is consistent with investigations of discrete stimuli in awake and behaving subjects. These studies utilize electrophysiological and electrochemical recordings to demonstrate pauses in dopamine neuron firing (Cohen et al, 2012;Matsumoto and Hikosaka, 2009;Mirenowicz and Schultz, 1996) and dopamine release (Badrinarayan et al, 2012;Roitman et al, 2008;Wheeler et al, 2011) in the NAc following discrete aversive stimuli. Our work extends these findings to include a dopamine-suppressive action of an agent, LiCl, which produces a long-lasting aversive state Tomasiewicz et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Discrete aversive stimuli evoke pauses in the firing rate of a clear majority of dopamine neurons (Cohen et al, 2012;Matsumoto and Hikosaka, 2009;Mirenowicz and Schultz, 1996) and suppress phasic dopamine release in the NAc (Badrinarayan et al, 2012;Oleson et al, 2012;Roitman et al, 2008;Wheeler et al, 2011; but also see Anstrom et al, 2009;Brischoux et al, 2009;Budygin et al, 2012;Park et al, 2015 for reported increases in phasic dopamine activity to aversive stimuli under some conditions). However, while discrete stimuli are commonly used to study phasic dopamine responses, the time domain of aversive stimuli can range from discrete to prolonged.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation